2015
DOI: 10.5812/hepatmon.15(5)2015.25328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Values of Elevated Serum Cytokeratin-18 Levels in Hepatitis: a Meta-Analysis

Abstract: Background:As an important intermediate filament protein within liver cells, cytokeratin-18 (CK-18) has been confirmed as a potential indicator in various hepatitis progressions.Objectives:We sought to clarify the connection between serum CK-18 levels and hepatitis pathogenesis in the present meta-analysis.Materials and Methods:With the application of various computerized databases, including PubMed, Embase, Cochrane Library, Google Scholar, Web of Science, China BioMedicine (CBM), China National Knowledge Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Serum CK-18 levels showed high sensitivity and specificity in diagnosing non-alcoholic steatohepatitis in patients with non-alcoholic fatty liver disease and reflected clinical disease more accurately than ALT levels [46, 47]. A meta-analysis of elevated serum cytokeratin-18 levels in hepatitis showed its clinical value for identifying the development of hepatitis [48]. The biomarkers such as CK-18, caspase 3/7 activity, sPD-1, and serum miR-122 levels could be used as adjunctive criteria to diagnose acute hepatitis C more definitively and to provide a sharper case definition for acute hepatitis C.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CK-18 levels showed high sensitivity and specificity in diagnosing non-alcoholic steatohepatitis in patients with non-alcoholic fatty liver disease and reflected clinical disease more accurately than ALT levels [46, 47]. A meta-analysis of elevated serum cytokeratin-18 levels in hepatitis showed its clinical value for identifying the development of hepatitis [48]. The biomarkers such as CK-18, caspase 3/7 activity, sPD-1, and serum miR-122 levels could be used as adjunctive criteria to diagnose acute hepatitis C more definitively and to provide a sharper case definition for acute hepatitis C.…”
Section: Discussionmentioning
confidence: 99%
“…A value of 25% -50% for I 2 indicates a low degree of heterogeneity, a value of 50% -75% indicates a moderate heterogeneity, and a value of > 75% indicates a high heterogeneity. When the I 2 value was > 50%, a random-effects model was used to pool the data; otherwise, a fixed-effects model was selected (20). The association between serum CK-18 M30 levels and CHB was estimated by the standard mean difference (SMD) with 95% confidence interval (CI).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Accumulated evidence suggests that hepatocyte apoptosis plays a vital role in chronic liver disorders (17,19). Yang et al found that the serum CK-18 levels might be a risk factor for non-alcoholic steatohepatitis (NASH), chronic hepatitis C (CHC), and chronic hepatitis B (CHB) (all P < 0.05) through conducting a meta-analysis of eight case-control studies (20). Some reports also showed that the plasma levels of CK-18 M30 were associated with the progression of non-alcoholic steatohepatitis (NASH) in non-alcoholic fatty liver disease (NAFLD) patients (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Yang et al found high serum CK‐18 in patients with liver disease compared to controls. More than that, increased serum CK‐18 was related to fibrosis progression ignoring family characteristics (Asians, Africans and Caucasians) and cause of liver disease (chronic hepatitis C, chronic hepatitis B and NASH).…”
Section: Discussionmentioning
confidence: 98%